THE MEANING OF HAWĀ IN THE QUR'AN PERSPECTIVE OF TAFSIR FI ZHILALIL QUR'AN BY SAYYID QUTHB AND ITS RELEVANCE TO ADULTERY - Saidatun Nisa; Zainal Arifin; Harun Al Rasyid (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the meaning of the word al-hawā in the Qur'an, the perspective of Tafsir Fi Zhilalil Qur'an by Sayyid Quthb and its relevance to Adultery. The phrase al-hawā is one of the important terms in the Qur'an that has various meanings and moral implications in human life. In the Qur'an, al-hawā is not only understood as a desire or impulse of the soul, but also as an inner tendency that if not controlled can drag people to moral deviations, including adultery. This study aims to analyze Sayyid Quthb's interpretation of the pronunciation of al-hawā, understand its implications on human behavior, and explain its relevance to the phenomenon of Adultery in the moral and spiritual perspective of Islam. This research is a library research with a qualitative approach and thematic method (maudhu'i). The primary data source is Tafsir Fi Zhilalil Qur'an by Sayyid Quthb, while secondary data sources come from relevant tafsir books, books, and scientific literature. The data analysis technique was carried out through descriptive-analytical analysis of the verses of the Qur'an that contain the utterance of al-hawā. The results of the study show that Sayyid Quthb interprets al-hawā as the desire of the soul that tends to drive people to transgressions, acts beyond the limits, and disobedience. According to him, following the hawā of lust is the root of moral and civilizational damage, when hawā is used as a standard of truth instead of revelation, injustice, moral deviation, and the destruction of the social order are born. Its relevance to Adultery lies in the view that it is a manifestation of the domination of lust over faith and reason. Therefore, controlling the desires of lust by structurally improving the order of life can prevent the occurrence of adultery.